Cooperation Between BPD And Village Government In The Formation Of Regulations In Mattirowalie Village - Safaruddin, Safaruddin; Aidah, Aidah (SEAN Institute, 2024)
This study aims to find out the cooperation between the village consultative body and the village government in the formation and implementation of village regulations in Mattirowalie Village, Tanete Riaja District, Barru Regency and to find out the factors that support it in Mattirowalie Village, Tanete Riaja District, Barru Regency. The type of research used is qualitative. Data collection techniques were obtained through interviews, observations and documentation. Data analysis techniques are data collection, data reduction, data presentation, and conclusion drawn. The results of this study show that the cooperation between the village consultative body and the village government in the formation and implementation of village regulations in Mattirowalie Village, Tanete Riaja District, Barru Regency, has been going well. This conclusion is based on the fulfillment of research indicators, namely partnership, consultation, and coordination. Meanwhile, the factors that support it are financing resources, apparatus resources, environmental resources, and clarity of target groups.